2021
DOI: 10.1016/j.omtn.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of M6A modification in the regulation of tumor-related lncRNAs

Abstract: An m 6 A writer is a protein complex with a high molecular weight of around 1 MDa, 25 which consists of the following core subunits: methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and their cofactors; Wilms' tumor 1-associating protein (WTAP); Vir like m 6 A methyltransferase associated (VIRMA); zinc finger CCCH-type containing 13 (ZC3H13); CBLL1 (also known as HAKAI); RNA-binding motif protein 15/15B (RBM15/15B); and the complex methylate mRNAs in a sequence context of RRACH (R = A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 150 publications
0
40
0
Order By: Relevance
“…Recently, various studies have identified a lot of differently expressed lncRNAs in BC and have been reported to be crucial orchestrators in the multistep process of BC tumorigenesis and malignant transformation. The m6A modification and lncRNA may play synergetic roles in tumorigenesis and development through a variety of regulatory mechanisms (9,12,14,15). For example, the m6A mediated by METTL3 was found to conduce to increase the expression of LINC00958, thereby aggravating the malignant phenotype of hepatocellular carcinoma (16).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies have identified a lot of differently expressed lncRNAs in BC and have been reported to be crucial orchestrators in the multistep process of BC tumorigenesis and malignant transformation. The m6A modification and lncRNA may play synergetic roles in tumorigenesis and development through a variety of regulatory mechanisms (9,12,14,15). For example, the m6A mediated by METTL3 was found to conduce to increase the expression of LINC00958, thereby aggravating the malignant phenotype of hepatocellular carcinoma (16).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are a class of non-coding RNAs greater than 200 nucleotides in length with limited or no protein-coding capacity that possess complex spatial structures and diverse functions ( Chen and Carmichael, 2010 ; Xie et al, 2021a ). Numerous studies have shown that lncRNAs play a significant role in biological functions, such as epigenetic modification, mRNA transcription, splicing, stability and translation ( Lan et al, 2021 ). Functionally, lncRNAs can either act in cis by regulating the expression of neighboring genes or in trans by regulating the expression of distant genes ( Ulitsky and Bartel, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that m 6 A modification could mediate muscle progenitor cell proliferation and differentiation. It has been demonstrated that m 6 A lncRNA modification plays roles in different biological processes ( Patil et al, 2016 ; Yang D. et al, 2018 ; Fazi and Fatica, 2019 ; Ma et al, 2019 ; He et al, 2020 ; Lan et al, 2021 ). However, little is known about the m 6 A methylation status of lncRNAs involved in developing skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there was a close correlation between lncRNAs and m6A regulators ( 24 , 29 ). Their interaction could regulate the expression of target genes as well as the cellular biological functions ( 21 , 32 , 33 ). Thus, in this study, we identified m6A-related lncRNAs to construct a risk model in LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…N6-Methyladenosine (m6A), as the most abundant and reversible RNA modification, is involved in the regulation of RNA splicing, localization, stability, and translation ( 19 , 20 ). m6A modification could regulate the expression and biological processes of mRNAs and non-coding RNAs ( 21 , 22 ). The m6A-regulated process was involved in three kinds of m6A regulators, which include methyltransferases (writers), demethylases (erasers), and m6A-binding proteins (readers).…”
Section: Introductionmentioning
confidence: 99%